AN UPDATE REVIEW: THE USE OF WET CUPPING THERAPY AGAINST VERTIGO - Nurona Azizah (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2018)
Vertigo is one of common complaints in the primary health care in the world. The common modern therapy for vertigo is using chemical pharmacological therapy yet having unwanted side effect. One of the wellknown complementary medicine that has been proven for relieving and curing many diseases is cupping therapy, especially wet cupping therapy. However, wet cupping therapy is not commonly applied in Indonesia healthcare. The causes may be due to the scarcity of the high quality scientific sources of the cupping therapy use for vertigo as well as the boundary between complementary and modern medicine in Indonesia. This review aimed to find out the use of wet cupping therapy against vertigo. A systematic review was obtained from NCBI and Google Scholar database (1999-2017) according to topic of interest. Yet Yunani, Persia, and China medicines recommend this therapy for treating vertigo as it had high level safety and effectivity. Wet cupping therapy has a potential effect in treating vertigo which the mechanism using negative pressure from vacuum cupping thus opening the skin barrier and removing causative pathology substances (CPS). Researchers and health practitioners essentially need to improve research in large scale towards the use of wet cupping against vertigo so the effectivity will be more optimal.Â